Genome Sequences of Five African Swine Fever Virus Genotype IX Isolates from Domestic Pigs in Uganda - Masembe, Charles; Sreenu, Vattipally B.; Filipe, Ana Da Silva; Wilkie, Gavin S.; Ogweng, Peter; Mayega, Francis J.; Muwanika, Vincent B.; Biek, Roman; Palmarini, Massimo; Davison, Andrew J. (Microbiology Resource Announcements, 2018)
Complete genome sequences of five African swine fever virus isolates were determined directly from clinical material obtained from domestic pigs in Uganda. Four sequences were essentially identical to each other, and all were closely related to the only known genome sequence of p72 genotype IX. African swine fever (ASF) is a contagious, highly lethal, hemorrhagic disease of domestic pigs caused by African swine fever virus (ASFV) (1). ASF results in up to 100% mortality. Its epidemiology is complex and adopts different patterns in Africa and Europe (2–6). The lack of effective interventions makes it extremely difficult to prevent or control and results in severe economic losses (7–11). ASFV is the sole member of the genus Asfivirus, family Asfarviridae, and has a linear, double-stranded DNA genome of 170 to 190 kbp (12, 13). There are currently 24 recognized genotypes (14, 15). Full genome sequences enable large strides toward developing control measures to use during epidemics. Available ASFV complete genome sequences number only 20, of which 3 are from eastern Africa (Kenya) but none are from Uganda, in which ASFV is also endemic. We present the first genome sequences of strains collected from domestic pigs in Uganda
Keywords: African Swine Fever; Virus Genotype; Domestic Pigs; Uganda